Using Spinner Game Media and Interactive Powerpoint in Improving Student Learning Outcomes in Pancasila Education - Muliani, Tri; Setiawan, Deni (Universitas Pendidikan Ganesha, 2025)
Monotonous, less innovative, and less diverse learning media make students less interested in learning, resulting in a lack of media that can help in understanding the material. This study examines the effectiveness of spinner media and interactive powerpoint learning outcomes for Pancasila Education in grade III Elementary Schools. This type of research is experimental research with a quasi-experimental design. The experimental design is a nonequivalent control group design. The study population was 56 students. The research sampling technique was purposive sampling. Class III B was the experimental class, and Class III A was the control class. Data collection techniques were in the form of test techniques (pretest and posttest). Non-test techniques were observation, interviews, questionnaires, and documentation. Initial data analysis techniques included normality and homogeneity, and final data analysis used t-test and N-Gain. The t-test results obtained a significance value of 0.000 (sig. (2-tailed) <0.05), so H0 was rejected and Ha was accepted. The N-Gain test results for the experimental class were 77.44%; they were effective, and the control class was 45.63%; they were less effective. In conclusion, learning using interactive spinner media and PowerPoint is effective. It has a higher average increase compared to learning without spinner media and interactive PowerPoint models on the learning outcomes of third-grade elementary school students.